Jurassic - Lower Cretaceous lithostratigraphic nomenclature for the Danish Central Trough - Jensen, Thorkild Feldthusen; Holm, Lise; Frandsen, Nils; Michelsen, Olaf (Danmarks Geologiske Undersøgelse Serie A, 1986)
The Jurassic and Lower Cretaceous sequences have been subdivided into lithostratigraphic units. The subdivision is primarily based on interpretation of petrophysical logs like gamma ray, sonic, neutron and density logs. The lithology descriptions are based on evaluation of logs and descriptions of cuttings samples, in a few intervals supplemented by sedimentological characteristics interpreted from core samples. Biostratigraphic analyses as well as seismic interpretations have been used for correlation from well to well and for description of the sediment bodies. As far as possible the lithostratigraphic units established in the adjacent regions have been extended into the Danish region. In the Jurassic sequence the following new formations are established: Lola Formation, Heno Formation, and Poul Formation. Furthermore, a hot unit is separated from the Farsund Formation. The Lower Cretaceous Valhall Formation is slightly emended, as the new Tuxen Formation and Sola Formation are separated from it. The lowest part of the Valhall Formation is defined as the Leek Member. Finally, the Vyl Formation is established as a formation marginal to the basin.